Cortical Thickness and Hippocampal Volume in Vascular and Non-vascular Depressed Patients - Egglefield, Dakota A.; Schiff, Sophie; Motter, Jeffrey N.; Grinberg, Alice; Rutherford, Bret R.; Sneed, Joel R. (Frontiers in Psychiatry, 2021)
Background: Reduced cortical thickness and hippocampal volume are prevalent markers of late life depression as well as mild cognitive impairment (MCI) but are conspicuously absent in the vascular depression (VD) literature. The present study aimed to determine differences in cortical thickness and hippocampal volume between VD and non-VD patients. Methods: Participants were enrolled in an 8-week open treatment antidepressant trial. 41 depressed individuals aged 50 and older underwent brain magnetic resonance imaging at baseline and were classified as VD or non-VD. Cortical thickness values for the left and right entorhinal, parahippocampal, and precuneal cortices, as well as left and right hippocampal volume, were linearly regressed on VD status to determine mean differences between VD and non-VD. Covariates included site, age, sex, and mean thickness or intracranial volume. Results: No statistical differences were found between VD and non-VD patients in cortical thickness of the bilateral precuneus, entorhinal, or parahippocampal cortices, or hippocampal volume (p > .001). Conclusions: The absence of statistical differences in grey matter between VD and non-VD patients raises several diagnostic, etiological, and developmental possibilities, namely that VD may not be connected with other late-life psychiatric illnesses such as MCI or dementia and that vascular disease may not be a common etiological risk factor for depression and dementia. Larger datasets, prospective longitudinal studies, and cognitively intact controls are needed to further address these types of questions.